Cambios en las propiedades nutricionales y tecno-funcionales de la harina de lenteja (Lens culinaris M.) Por efecto de la imbibición - Morales Herrejón, Yuliza Guadalupe (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
In Mexico, Michoacán is the main producer of lentils (Lens culinaris M) with 93% of national production. Lentils play an important role in human nutrition, in addition to providing food security and being a sustainable crop. Lentils contain a high percentage of protein (25-35 %). They are rich in amino acids: arginine, aspartic acid, glutamic acid and lysine. Compared to other legumes, they contain dietary fiber, vitamins, minerals, bioactive compounds, among others. The composition of lentils can change with respect to the variety of the seed, on the other hand, they contain anti-nutritional compounds that affect the protein quality, bioavailability, digestive and metabolic utilization of nutritional compounds. However, many of these compounds have antioxidant activity (AOX) and are mostly attributed to total polyphenols (TP). The nutritional quality of lentils may differ with respect to the variety and the processing for which it is intended. Lentils are generally consumed later, when processed by hydro-thermal cooking. Another processing procedure for the legume is soaking (imbibition), which precedes cooking. Studies suggest that imbibition increases protein digestibility and promotes the elimination or reduction of anti-nutritive components, improving protein bioavailability. There are also technological treatments that increase digestibility and improve the nutritional, sensory and techno-functional qualities of legumes. The objective of this research was to characterize lentils of green and red varieties, evidencing the presence of compounds with nutritional and functional character, and to determine the effect of lentil imbibition on protein fractions, dietary fiber, AOX and techno-functional properties. The study material was two varieties of lentils: red and green. Initially, lentils were pulverized and characterized by proximate chemical analysis: (AOAC, 2005). Subsequently for the imbibition treatments, green and red lentils were imbibed at 50 °C for 1, 2, 3 and 4 hours, subsequently dehydrated at 70°C. Green lentils, compared to red lentils, had a higher nutritional value and physiological activity in terms of protein and dietary fiber content. The flour imbibed at 1h obtained the lowest TDF content (25.03%), with no significant difference with respect to the raw flour. In the imbibed flours of the red variety, a decrease in TDF was observed with respect to the cooked flour. PT and AOX decreased in the flour of both lentil varieties. In relation to CAAc there was no difference (p≤0.05) with respect to control and imbibed flours for both varieties. Luminosity was found to be white positive, there was no difference between control and imbibed flours. The flours presented yellow tonality, however, the red lentil flour had red tonalities. Finally, the SEM results indicate that the imbibed flours, as well as the lentils cooked, presented greater changes in the morphology of the starch granules, which are reflected in the changes in the techno-functional properties of the food matrix, due to the changes in the starch granules and proteins.

En México, Michoacán es el principal productor de lenteja (Lens culinaris M.) con 93 % de la producción nacional. La lenteja es nutritiva, brinda seguridad alimentaria y es cultivo sostenible. Contienen un alto porcentaje de proteína (25-35 %), son ricas en aminoácidos: arginina, ácido aspártico, glutámico y lisina. Contiene fibra dietaria, vitaminas, minerales, compuestos bioactivos, entre otros. La lenteja presenta además componentes anti-nutricionales que afectan la calidad proteica, biodisponibilidad, utilización digestiva y metabólica de estas y otros compuestos nutritivos. Sin embargo, los anti-nutricios tienen actividad antioxidante (AOX) y en su mayoría se atribuye a los polifenoles totales (PT). La calidad nutricional de la lenteja puede diferir con respecto a la variedad y el procesamiento al que se le destine. Las lentejas generalmente son consumidas después de procesarse por cocción hidro-térmica. Otro de los procedimientos de transformación es el remojo (imbibición) que antecede a la cocción. La imbibición puede aumentar la digestibilidad proteica y la eliminación o reducción de componentes anti-nutritivos mejorando la biodisponibilidad proteica, la digestibilidad, las cualidades nutricionales, sensoriales y tecno-funcionales de las legumbres. El objetivo de la presente investigación fue determinar el efecto de la imbibición de lenteja (Lens culinaris M.) de dos variedades sobre el valor nutricional y sus propiedades tecno-funcionales como harina. Se utilizaron dos variedades de lentejas: roja y verde. Las lentejas se caracterizaron mediante un análisis químico proximal: (AOAC, 2005). Posteriormente las lentejas fueron imbibidas a 50 °C por 1, 2, 3 y 4 horas, deshidratadas a 70°C y pulverizadas para la obtención de harina. Los controles fueron Control 1: lenteja cruda y Control 2: lenteja cocida. La lenteja verde con respecto a la roja presenta un mayor valor nutricional y de actividad fisiológica, referido a su contenido en proteína y fibra dietaria. La imbibición a 2 h promueve los mayores cambios nutricionales, tecno-funcionales y morfológicos en la matriz alimentaria, harina de lenteja.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FQFB-M-2024-0535; Fracciones proteicas; Propiedades tecno-funcionales; Antinutricionales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18664